2019
DOI: 10.1016/j.chest.2019.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cough and Gastroesophageal Reflux in Children

Abstract: BACKGROUND: Whether gastroesophageal reflux (GER) or GER disease (GERD) causes chronic cough in children is controversial. Using the Population, Intervention, Comparison, Outcome (PICO) format, we undertook four systematic reviews. For children with chronic cough (> 4-weeks duration) and without underlying lung disease: (1) who do not have gastrointestinal GER symptoms, should empirical treatment for GERD be used? (2) with gastrointestinal GER symptoms, does treatment for GERD resolve the cough? (3) with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
(33 reference statements)
1
23
0
3
Order By: Relevance
“…Частота встречаемости кашля, ассоциированного с гастроэзофагеальным рефлюксом, у детей варьирует от единичных случаев до 10-35% [40]. Таким образом, помимо ЛОР-патологии причиной синдрома «кашля верхних дыхательных путей» может быть и патологический гастроэзофагеальный рефлюкс [41,42,43].…”
Section: Discussionunclassified
“…Частота встречаемости кашля, ассоциированного с гастроэзофагеальным рефлюксом, у детей варьирует от единичных случаев до 10-35% [40]. Таким образом, помимо ЛОР-патологии причиной синдрома «кашля верхних дыхательных путей» может быть и патологический гастроэзофагеальный рефлюкс [41,42,43].…”
Section: Discussionunclassified
“…GOR is commonly reported as a cause of a cough in adult populations. There is a lack of evidence for it as a cause of a chronic cough in otherwise healthy children (Chang et al., 2019), but it may be a cause in adolescents. It is suggested that reflux stimulates a cough by acid causing irritation of the upper respiratory tract, or by aspiration in the lower respiratory tract.…”
Section: Causes Of Chronic Coughmentioning
confidence: 99%
“…regurgitation, heartburn or epigastric pain, or neck posturing in infants). GOR treatment may be trialled for 4 to 8 weeks and reassessed, if other causes of cough are excluded (Chang et al., 2019). There is evidence however that overuse of proton pump inhibitors can increase risk of infections, cause vitamin B12 deficiency, and increase fracture risk (Chang et al., 2019).…”
Section: Causes Of Chronic Coughmentioning
confidence: 99%
“…Наукові дослідження свідчать про кращу можливість контролю БА в дітей після відповідного лікування ГЕРХ [3,5]. Вчені наго лошують на важливості призначення лікарсь ких препаратів для лікування ГЕРХ у дітей саме за наявності клінічних симптомів цієї патології з метою уникнення серйозних побіч них явищ [1]. Враховуючи вищезазначене, необхідно проводити більш ретельне обстежен ня та лікування дітей з коморбідною БА.…”
Section: вступunclassified